KEMAMPUAN KOMUNIKASI PUSTAKAWAN DALAM PENCARIAN KOLEKSI KAITANNYA DENGAN KUALITAS LAYANAN DI PERPUSTAKAAN GEMILANG SMPN 1 BANGUNTAPAN - Imroatun Shaleha; Anis Masruri (Unversitas Muhammadiyah Mataram, 2023)
This study aims to determine the communication skills of librarians in relation to service quality in the search for collections at the Gemilang Library. This research method uses a descriptive qualitative method. Data collection techniques with observation, interviews, and documentation. The results of this study based on Garperz's theory are ten in service quality. As for the ten points, there are seven points that have been implemented, including politeness and friendliness, responsibility, ease of service, variations in service models, personal service, convenience in obtaining service, and service supporting attributes. Efforts made as a librarian in increasing user satisfaction at the Gemilang Library, by means of librarian guidance or training, one of which is BIMTEK. In addition, continue to improve self-quality by learning, increasing the network of friends, innovating and finally by communicating well with users.Keywords: Competency, PersonalityService qualitYCommunication